Gamma-ray, stable carbon and oxygen isotope chemostratigraphy and sequence stratigraphy of the Lower Mahil Formation (KS-1 Khuff-Equivalent), Northern Oman - Moustafa, Mohamed S. H.; Al Raqaishi, Rasha; El-Ghali, Mohamed A. K.; Gharbi, Mohamed; Abbasi, Iftikhar Ahmed; Al Humaidi, Aaraf; Al Ghafri, Nada; Alshukaili, Marwa Musallam; Al-Awah, Hezam (Frontiers in Earth Science, 2023)
This research presents findings from a study focused on the Lower Triassic (Induan) Lower Mahil KS-1 Formation, situated on a homoclinal carbonate platform in Northern Oman. The sequence stratigraphy of this formation is characterized by a considerable thickness variation, slumps, and breccia deposits related to active normal faults coupled with intra-basin growth faults. The main objective was to establish a reliable stratigraphic framework for the Lower Mahil KS-1 Formation by integrating high-resolution carbon isotope data along with high-resolution spectral and total gamma-ray data. To achieve this, whole-rock samples were analyzed for δ13C and δ18O isotopes. Spectral and total gamma-ray records were obtained for the formation. Isotope sampling is conducted every 0.5 m in the Saiq Plateau and Wadi Sahtan sections. Furthermore, spectral gamma-ray measurements were taken at intervals of 10 cm from the logged sections. Within the third-order sequence, the spectral gamma-ray data revealed a distinct sea-level trend, leading to the division of KS1 into two different parts. Five fourth-order depositional sequences were identified by analyzing stable carbon isotopes, uranium, and total gamma-ray profiles. Four of these sequences displayed complete patterns, reflecting transgression and regression phases, while the fifth sequence was incomplete and solely comprised a transgressive phase. An essential outcome of the study is the correlation of the δ13C curve of the Lower Mahil KS-1 Formation with other similar formations around the Tethys region. This correlation indicates that the Lower Mahil KS-1 Formation captures the near-primary signal of carbon isotope variations in coeval seawater. As a result, it holds promise as a reference section for future investigations and studies in this field. Compared to the prior investigation, this study utilizes data with higher precision, capturing spectral gamma-ray measurements at 10 cm intervals and isotope measurements at 50 cm intervals. Furthermore, the study’s focus is confined explicitly to KS1.